Morphological, physiological, and biochemical responses of three different soybean (Glycine max L.) varieties under salinity stress conditions - Kokebie, Desilal; Enyew, Abiyu; Masresha, Getinet; Fentie, Tarekegn; Mulat, Emebet (Frontiers in Plant Science, 2024)
Salinity is one of the most detrimental factors for the growth performance and productivity of crops worldwide. Therefore, understanding crop responses or growth potentials and their effectiveness in salinity mitigation is highly important for the selection of salinity-tolerant plant varieties. In this study, the effects of salinity at various stress levels (0 mM, 50 mM, 100 mM, and 150 mM NaCl) on the morphological, physiological, and biochemical parameters of three soybean varieties (‘Afigat’, ‘Gishama’, and ‘Pawi-2’) were investigated. The results showed that salinity significantly reduced morphological traits including plant height, number of leaves per plant, stem thickness, shoot and root length, and fresh and dry weight. This reduction was more prominent in the ‘Afigat’ variety for all of these traits except shoot and root length. The concentrations of chlorophyll a and b decreased with increasing salinity. In addition, salinity significantly increased leaf electrolyte leakage (EL), lipid peroxidation, proline accumulation, and phenol and flavonoid content. The ‘Pawi-2’ variety was more tolerant than the other studied varieties in terms of membrane stability (less EL and a low malondialdehyde content) and proline, phenol, and flavonoid accumulation. Therefore, ‘Pawi-2’ may be considered as the most salt-tolerant variety in comparison with the other studied soybean varieties. Further complementary studies in field conditions including anatomical parameters are needed to confirm these findings.